PENGENALAN PEMANFAATAN PENJUALAN MELALUI E-COMMERCE DI SMK FADILAH - Bambang Santoso; Alvino Octaviano; Sofa Sofiana; Muhammad Cordiaz; Herdyanto Herdyanto (JAMAIKA: JURNAL ABDI MASYARAKAT, 2022)
The purpose of this Community Service is to increase the awareness of SMK students about e-commerce. Because one of the goals of SMK is to prepare graduates who are ready to use in the community. Both as a worker and as an entrepreneur.The place of service is a vocational school, namely Fadilah Vocational School, in Pondok Aren, South Tangerang. The problem raised in this service is the importance of recognizing e-commerce. There are many kinds of e-commerce to choose from to increase sales. One of them is the market place. For beginners, the market place is a place that must be taken into account because apart from being easy, all e-commerce facilities are already available there. In addition to the many users, entering the market is no longer difficult. Selling through e-commerce is now considered mandatory. Most of the Indonesian people, especially the younger generation, have used e-commerce as a place to shop. Walking to shop from shop to shop has greatly diminished for the younger generation, being replaced by virtual shop to shop. So e-commerce is a field that is worth understanding and mastering by entrepreneurs. It is hoped that in the future students will be able to understand the importance of e-commerce, be able to weigh between several available e-commerce options, and ultimately be able to use this technology to increase business sales.